Perancangan Dashboard Visualisasi Data Key Performance Indicator (KPI) Menggunakan Looker Data Studio Studi Kasus PT. Sicepat Ekspres - Mukhlis Aryanto; Atang Susila (CV. Multi Kreasi Media, 2024)
At PT. Sicepat Ekspres KPI (Key Performance Indicator) system and mechanism have not been formed in a structured and systematic manner, so it is not flexible in conducting data analysis. With the KPI dashboard information find out the performance of each member of the IT Helpdesk team. Based on the Key Performance Indicators (KPI), information on the results of the decision will automatically appear whether members of the IT Helpdesk team have good performance or not. The method used in this study is quantitative because the research is descriptive and focuses on data analysis and data visualization. The results of the complaint tickets handled by the IT helpdesk team from November 6, 2022, to November 13 2022 were 2,477 tickets, and 275 tickets were escalated. complaints are on the